2020
DOI: 10.1073/pnas.1908158117
|View full text |Cite
|
Sign up to set email alerts
|

High-dose ascorbic acid synergizes with anti-PD1 in a lymphoma mouse model

Abstract: Major efforts are underway to identify agents that can potentiate effects of immune checkpoint inhibition. Here, we show that ascorbic acid (AA) treatment caused genomewide demethylation and enhanced expression of endogenous retroviral elements in lymphoma cells. AA also increased 5-hydroxymethylcytosine (5hmC) levels of CD8+ T cells and enhanced their cytotoxic activity in a lymphoma coculture system. High-dose AA treatment synergized with anti-PD1 therapy in a syngeneic lymphoma mouse model, resulting in mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 51 publications
3
92
0
Order By: Relevance
“…ccRCC is characterized by deletions and under-expression of L-2-hydroxyglutarate dehydrogenase (L2HGDH) which results in the aberrant accumulation of L-2-hydoxyglutarate (L2HG) 44 . L2HG competitively inhibits the Ten-Eleven-Translocation (TET) enzymes, including TET2, which has been shown to have an important role in cancer immunity 15,45 . ccRCC is also characterized by loss of succinate dehydrogenase resulting in the accumulation of oncogenic succinate, which also inhibits the TET enzymes, further contributing to the widespread genomic aberrant hypermethylation in the malignancy 46,47 .…”
Section: (Iv) Tumor-associated Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…ccRCC is characterized by deletions and under-expression of L-2-hydroxyglutarate dehydrogenase (L2HGDH) which results in the aberrant accumulation of L-2-hydoxyglutarate (L2HG) 44 . L2HG competitively inhibits the Ten-Eleven-Translocation (TET) enzymes, including TET2, which has been shown to have an important role in cancer immunity 15,45 . ccRCC is also characterized by loss of succinate dehydrogenase resulting in the accumulation of oncogenic succinate, which also inhibits the TET enzymes, further contributing to the widespread genomic aberrant hypermethylation in the malignancy 46,47 .…”
Section: (Iv) Tumor-associated Metabolitesmentioning
confidence: 99%
“…Agents that have shown remarkable pre-clinical efficacy in combination with checkpoint inhibition but are not 'patentable' or 'profitable' have a markedly tougher road to effective translation-even if they have been shown to be safe and well-tolerated in cancer patients. As an example, high dose ascorbic acid has been recently shown to synergistically enhance the efficacy of checkpoint inhibition 15,97 , is known to be safe and well tolerated in cancer patients 98 , and deserves clinical exploration in combination with checkpoint inhibition. However, financial considerations and logistics impede such exploration.…”
Section: (Iv) Financial Considerations and Logisticsmentioning
confidence: 99%
“…Parallel to local regional hyperthermia patients received 3 times weekly high dose vitamin C intravenously (0.5 g/ kg) and alpha lipoic acid 600 mg. High-dose vitamin C has been suggested as an adjuvant cancer treatment as it is toxic to tumor cells, since it targets many of the mechanisms that cancer cells utilize for their survival and growth. High-dose vitamin C delays cancer growth by enhancing infiltration of the tumor microenvironment by immune cells and cooperates with immune checkpoint therapy (ICT) in several cancer types [23][24][25][26]. Lipoic acid synergistically enhanced ascorbate cytotoxicity [27] and inhibited the enzyme pyruvate dehydrogenase kinase that is particularly upregulated in cancer cells and is the major determinant of the "Warburg effect", thus contributing to a higher vulnerability/decreased resilience of the neoplasm [28].…”
Section: Treatmentmentioning
confidence: 99%
“…The combination of anti-PD-L1 monoclonal antibody and oltipraz or bezafibrate, two ligands of the PGC1α/Nrf2 and PGC1α/PPAR complexes, respectively, resulted in augmented tumor-suppression activity compared to either treatment alone, explained by the significant increase in both mitochondrial metabolism and glycolysis, driven by PGC1α/PPAR signaling [105]. Other studies showed that high-dose vitamin C in mouse tumor models synergized with anti-PD-1 to enhance cancer immunotherapy, but the exact mechanism of action remains unclear [106,107]. Similarly, adding metformin to PD-1 blockade regimen resulted in enhanced T cell anti-tumor immunity and tumor clearance in murine models by decreasing intra-tumoral hypoxia.…”
Section: Balancing Metabolism Of Ros In Favor Of T Cell Functionmentioning
confidence: 99%